2021
DOI: 10.1155/2021/6647258
|View full text |Cite
|
Sign up to set email alerts
|

Senkyunolide I Protects against Sepsis‐Associated Encephalopathy by Attenuating Sleep Deprivation in a Murine Model of Cecal Ligation and Puncture

Abstract: Sepsis may lead to sleep deprivation, which will promote the development of neuroinflammation and mediate the progression of sepsis-associated encephalopathy (SAE). Senkyunolide I, an active component derived from an herb medicine, has been shown to provide a sedative effect to improve sleep. However, its role in sepsis is unclear. The present study was performed to investigate whether Senkyunolide I protected against SAE in a murine model of cecal ligation and puncture (CLP). Here, we showed that Senkyunolide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 33 publications
(14 reference statements)
1
14
0
Order By: Relevance
“…The mice were housed in SD devices under an LD cycle as previously described. 51 , 53 , 54 After two weeks of acclimatization, the mice were divided into four groups including the non-SD group, the SD group, a forced-recovery-in-normal-sleep-condition (SD-FR-NSC) mouse model for four weeks after the four weeks of SD, and a normal-sleep-condition (SD-NSC) mouse model for four weeks after the four weeks of SD. For the SD group, the sweep bar worked every 1.5 minutes during the light cycle (ZT0–12) for four weeks.…”
Section: Methodsmentioning
confidence: 99%
“…The mice were housed in SD devices under an LD cycle as previously described. 51 , 53 , 54 After two weeks of acclimatization, the mice were divided into four groups including the non-SD group, the SD group, a forced-recovery-in-normal-sleep-condition (SD-FR-NSC) mouse model for four weeks after the four weeks of SD, and a normal-sleep-condition (SD-NSC) mouse model for four weeks after the four weeks of SD. For the SD group, the sweep bar worked every 1.5 minutes during the light cycle (ZT0–12) for four weeks.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, it has been reported that the progression of SAE could lead to the secretion of pro-inflammatory cytokines [27, 32]. In addition, IL-1β, IL-6, and TNF-α levels were upregulated during the development of SAE [32]. Thus, these 3 cytokines were selected for analysis in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Another research also demonstrated that Emodin attenuated LPS-induced apoptosis and inflammation in ATDC5 cells [13]. On the other hand, it has been reported that the progression of SAE could lead to the secretion of pro-inflammatory cytokines [27, 32]. In addition, IL-1β, IL-6, and TNF-α levels were upregulated during the development of SAE [32].…”
Section: Discussionmentioning
confidence: 99%
“…The FCT was performed following the protocol as previously described [54,55]. On the day of training, mice were placed into an enclosed training chamber and allowed to explore for 180 s. Mice were then exposed to a tone (30 s, 70 dB, 3 kHz), followed by a 2 s foot shock (0.45 mA).…”
Section: Behavioral Testsmentioning
confidence: 99%